Step
*
2
1
of Lemma
qdiv-qdiv
.....assertion..... 
1. a : ℚ
2. b : ℚ
3. c : ℚ
4. ¬(b = 0 ∈ ℚ)
5. ¬(c = 0 ∈ ℚ)
6. ¬((b/c) = 0 ∈ ℚ)
⊢ a = ((a * c/b) * (b/c)) ∈ ℚ
BY
{ xxx(Subst' (b/c) = (b * (1/c)) ∈ ℚ 0 THENA Auto)xxx }
1
.....equality..... 
1. a : ℚ
2. b : ℚ
3. c : ℚ
4. ¬(b = 0 ∈ ℚ)
5. ¬(c = 0 ∈ ℚ)
6. ¬((b/c) = 0 ∈ ℚ)
⊢ (b/c) = (b * (1/c)) ∈ ℚ
2
1. a : ℚ
2. b : ℚ
3. c : ℚ
4. ¬(b = 0 ∈ ℚ)
5. ¬(c = 0 ∈ ℚ)
6. ¬((b/c) = 0 ∈ ℚ)
⊢ a = ((a * c/b) * b * (1/c)) ∈ ℚ
Latex:
Latex:
.....assertion..... 
1.  a  :  \mBbbQ{}
2.  b  :  \mBbbQ{}
3.  c  :  \mBbbQ{}
4.  \mneg{}(b  =  0)
5.  \mneg{}(c  =  0)
6.  \mneg{}((b/c)  =  0)
\mvdash{}  a  =  ((a  *  c/b)  *  (b/c))
By
Latex:
xxx(Subst'  (b/c)  =  (b  *  (1/c))  0  THENA  Auto)xxx
Home
Index